The extent to which pricing policy and strategy influence revenue generation of life assurance firms: Desktop study - Murwira M Tsitsi; Wadesango Newman; Sitsha Lovemore (AnKa Publisher, 2023)
Pricing policies and strategies are vital tools to confront competitive pressures in a market environment and also as a tool of improving the performance of the funeral sector. Funeral Assurances need to implement a pricing policy or strategy that maximize revenue but remain competitive in the target market. Therefore, the purpose of this study was to investigate the extent to which pricing policy and strategy influence revenue generation of life assurance firms. This desktop study has successfully explored the factors that influence the implementation of pricing policies and strategies used by the funeral sectors. It emerged that in order to curve competition in the market, insurance firms should provide complete quality services to policyholders to add value to customers thereby maximising revenue. The results also showed that dynamic pricing is the best for premium pricing even if it was not yet implemented by life assurance firms. The study recommends that the prices charged for funeral cover packages by the funeral assurance companies should be affordable to all individuals including the low-income earners so that there would generate more revenue